Science Teachers’ Perceptions of Social Media Platforms: An Exploration of Educational Instagram Pages - Doğru, M. Said; Yüzbaşıoğlu, Fatih (Springer Science and Business Media LLC, 2023)
Abstract
Instagram is one of the most widely used social media platforms around the world. It is not only a platform for users who want to spend time on social media, but also a platform where educators come together. This study aims to examine the views of science teachers on educational Instagram accounts. The sample was composed of 972 secondary science teachers and the data were collected through an online survey. The findings obtained from the online survey revealed the types of Instagram pages the participants valued the most, the criteria they used to select them, and the features they liked and disliked on these pages. The findings indicate that the participants generally benefit from Instagram in sharing resources related to science, communicating with their colleagues, following current information about their field of science, and contributing to their professional development. In addition, some of the features disliked by the participants about Instagram included late responses from administrators, off-topic posts and comments on the pages, and some limitations imposed by the platform. Overall, most of the participants find science-related Instagram pages valuable because they think that these pages increase their field-specific competencies. In conclusion, Instagram pages can be considered as a platform that can contribute to the professional development of science teachers specifically, and all teachers in general.
Keywords: 4. Education; 16. Peace & justice